How Elementary School Teachers Assess Students’ Affective Domain in the Classroom during Distance Learning?: A Phenomenological Study - Ningrum, Dita Salsavira Cahaya; Senen, Anwar; Ambarwati, Dewi; Izhar, Gusti; Nawangsari, Nada Savitri (Jurnal Pendidikan Progresif, 2022)
How Elementary School Teachers Assess Students’ Affective Domain in the Classroom during Distance Learning?: A Phenomenological Study Objectives: This study aims to describe how elementary school teachers assess students' affectiveness, especially in social studies learning during distance learning. Methods: This research is phenomenology study, data collection techniques using interviews and document studies. Subject 5 elementary school teacher participants. The data analysis technique uses qualitative data analysis. Findings: The teacher conducts an affective assessment during social studies learning on student behavior, there still a problem, the teacher cannot monitor students directly so that the affective assessment in learning cannot be carried out optimally. However, affective assessment provides the benefit that the teacher can direct good attitudes and character to students. Conclusion: Cooperation of various parties to maximize affective assessment in the social studies learning process in the distance learning period.Keywords: affective assessment, social studies, elementary school teachers, distance learning. DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202224